Production and marginal analysis of lactating cows subjected to dietary cation-anion balances - Figueiredo, Cibelle Borges; Santana Junior, Hermógenes Almeida de; Mendes, Fabrício Barcelar Lima; Cardoso-Santana, Elizângela Oliveira; Viana, Pablo Teixeira; Motta, Thiago Pereira; Abreu Filho, George (Acta Scientiarum. Animal Sciences, 2021)
The objective of this study was to evaluate productive, nutritional, and economic traits in lactating cows on pasture fed diets with different cation-anion balances (DCAB). Ten lactating ¾ Holstein × ¼ Dairy Gyr cows in the middle third of lactation, at an average age of 70 ± 4.6 months and an average body weight of 400 ± 55.2 kg, were distributed into five treatments in a 5 × 5 Latin square experimental design with two simultaneous squares. Treatments consisted of diets with DCAB of +237, +258, +294, +347, or +419 mEq dry matter (DM). No effects of intake were observed. There was no significant effect of DCAB on milk yield. The milk protein content was not influenced by the DCAB. Body condition score was not significantly affected by the DCAB. The apparent digestibilities of dry matter and nutrients (crude protein, neutral detergent fiber, ether extract, non-fibrous carbohydrates, and total digestible nutrients) were not affected by the DCAB. Marginal rate of return did not show significant differences. Under good conditions of pasture, forage availability, and quality associated with the lactation phases of the cows, all diets were efficient in milk production, dry matter intake, and digestibility. However, in economic terms, the most attractive DCAB was +237 mEq kg-1 DM.